2018
DOI: 10.3727/096504017x14944585873631
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA SChLAP1 Accelerates the Proliferation and Metastasis of Prostate Cancer via Targeting miR-198 and Promoting the MAPK1 Pathway

Abstract: Prostate cancer has become the most commonly diagnosed and the second leading cause of cancer-related deaths in males. The long noncoding RNA second chromosome locus associated with prostate-1 (SChLAP1) has been found to be overexpressed in a subset of prostate cancer. However, the significance and mechanism of SChLAP1 in prostate cancer are not well known. In this study, we explored the role of SChLAP1 in prostate cancer tissues, cell lines, and mouse models. The effect of SChLAP1 on miR-198 and MAPK1 was spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 34 publications
0
45
0
Order By: Relevance
“…Previous research has shown that ULK2 and ATG4D were hub autophagy genes, which are necessary for maximal androgen-mediated autophagy and cell proliferation and also associated with poor prognosis in PCa [14]. Li et al demonstrated that MAPK1 plays an important role in regulating cancer cell invasion and metastasis in vitro and in vivo [20]. Forkhead box transcription factor-1 (FOXO1) is a tumor suppressor that is downregulated in human prostate cancer, which acts as a repression target of EZH2 and an essential mediator of EZH2 inhibition-induced cell death [21].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown that ULK2 and ATG4D were hub autophagy genes, which are necessary for maximal androgen-mediated autophagy and cell proliferation and also associated with poor prognosis in PCa [14]. Li et al demonstrated that MAPK1 plays an important role in regulating cancer cell invasion and metastasis in vitro and in vivo [20]. Forkhead box transcription factor-1 (FOXO1) is a tumor suppressor that is downregulated in human prostate cancer, which acts as a repression target of EZH2 and an essential mediator of EZH2 inhibition-induced cell death [21].…”
Section: Discussionmentioning
confidence: 99%
“…4c, we did not observe any significant increase in cell proliferation after LINC00844 depletion. While many reported lncRNAs in prostate cancer are known to affect cell proliferation and migration [26,31], our results show LINC00844 affects exclusively prostate cancer cell migration and invasion, without affecting cell proliferation. Collectively, these results suggest that LINC00844 (i) is critical for preventing a metastatic phenotype in prostate cancer cells and (ii) mediates its effects through the AR signaling pathway.…”
Section: Linc00844 Inhibits Cell Migration and Invasionmentioning
confidence: 47%
“…For example, it has been reported that miR543, miR217, and miR20b served as tumor suppresser miRNAs by targeting ERK2 in cancers of breast, colon/rectum, or thyroid. The microRNAs miR198, miR329‐3p, and miR634 also target ERK2, suppressing tumor cell proliferation, migration, and invasion, or restoring drug sensitivity in prostate, uterine cervical, and ovarian cancers. RSK2 is a target of miR375 and miR634 .…”
Section: Discussionmentioning
confidence: 99%